Hemodialysis Adherence and Quality of Life Among Patients with Chronic Kidney Disease in Indonesia: A Cross-Sectional Study - Desi Rusiana Alfiani; Ema Agustin; Fransiska Haryati; Titi Permaini; Rodiyanah Rodiyanah; Agni Laili Perdani (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Chronic kidney disease requires long-term hemodialysis, yet adherence to treatment remains a persistent challenge that may influence patient-reported outcomes. Objective: This study aimed to examine the relationship between hemodialysis adherence and quality of life among patients with chronic kidney disease in Indonesia. Methods: A cross-sectional study was conducted from January to February 2025 in a public hospital. Fifty-two patients undergoing maintenance hemodialysis were recruited using convenience sampling. Adherence was assessed through medical record review, including session attendance and completion. Quality of life was measured using the Kidney Disease Quality of Life Short Form-36 (KDQOL-SF36). Data were analyzed using Pearson’s correlation and linear regression. Results: The mean quality of life score was 67.06 ± 9.82. Hemodialysis adherence was positively correlated with overall quality of life (r = 0.36, p = 0.05). Higher adherence was particularly associated with symptom-related and disease impact domains. Regression analysis indicated that adherence significantly predicted quality of life with (β = 0.20, p < 0.05, R² = 0.04), indicating that adherence explained 4% of the variance in quality of life scores Conclusion: Adherence to hemodialysis is significantly associated with better quality of life among patients with chronic kidney disease. These findings highlight the importance of adherence monitoring and patient-centered interventions in hemodialysis care.